2017
DOI: 10.1016/j.rser.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fuel properties on the basis of fatty acid profiles of oleaginous yeast for potential biodiesel production

Abstract: A B S T R A C TOver the last decade, there has been a huge upsurge of interest in sustainable production of biomass-based biofuels to fulfill the existing energy demand and simultaneously reducing the environmental deterioration. Earlier, vegetable oils and animal fats were utilized for biodiesel production, but due to food crisis and environmental sustainability, renewable sources such as neutral lipid derived from microbes are gaining much attention for budding biodiesel industries. Among various types of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
111
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(118 citation statements)
references
References 141 publications
(180 reference statements)
3
111
0
4
Order By: Relevance
“…other hexoses, disaccharides, glycerol, polysaccharides, etc. ;Ratledge 1988;Aggelis 2011a, 2011b;Patel et al 2017a). Lipids produced by the above-men tioned micro-organisms, addressed also as single cell oils (SCOs), present a continuously increasing interest concerning aspects of both applied and basic research (Moreton 1988; Ratledge and Wynn 2002;Ratledge and Cohen 2008;Aggelis 2011a, 2011b;Xu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…other hexoses, disaccharides, glycerol, polysaccharides, etc. ;Ratledge 1988;Aggelis 2011a, 2011b;Patel et al 2017a). Lipids produced by the above-men tioned micro-organisms, addressed also as single cell oils (SCOs), present a continuously increasing interest concerning aspects of both applied and basic research (Moreton 1988; Ratledge and Wynn 2002;Ratledge and Cohen 2008;Aggelis 2011a, 2011b;Xu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…sugars, glycerol, etc.) are considered as potential and important candidates for the production of this lipid that would result in the generation of the second-generation lipid-based biofuels (Huang et al 2013;Meeuwse et al 2013;Xu et al 2013;Koutinas et al 2014a;Muniraj et al 2015a;Patel et al 2016Patel et al , 2017aQin et al 2017). It is evident that concerning the production of liquid biofuels with the aid of oleaginous micro-organisms, only the hydrophilic carbon sources should be used as substrates for this purpose; it would evidently not make sense to proceed to fermentation of a fatty substrate in order to create cellular lipid that would subsequently be converted into biofuel (biodiesel or renewable diesel), while the initial fat substrate could have already been directly converted into biofuel without the step of fermentation being implicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It implied that the greatest contributor to the final cost was utilities followed by raw materials. It was different from other studies which reported that the cost was mainly from the raw materials (up to 50-70% of the total cost) (Madani et al, 2017;Patel et al, 2017;Živković et al, 2017). It would be due to that the lipid source in the study was wastewater sludge which was cost free.…”
mentioning
confidence: 57%
“…In addition, without taking credit, the biodiesel production cost was 1.08 US $/kg (0.94 US $/L) with 17.07% from raw materials, 30.73% from equipment, 6.39% from labor, 0.96% from lab/QC/QA, 44.47% from utilities, and 1.38% from waste treatment. The cost was higher than the commercial biodiesel derived from soybean which was 0.92 US $/kg biodiesel (Patel et al, 2017). Compared to the biodiesel produce from the lipid directly extracted from the sludge (0.67 US $/kg biodiesel), the cost of biodiesel production from the lipid accumulated in the microorganism cultivated with sludge was higher.…”
Section: Discussionmentioning
confidence: 85%